FINANCIAL DISTRESS AND EARNINGS MANAGEMENT IN INDONESIA: THE ROLE OF INDEPENDENT COMMISSIONERS - Vania Agatha Rusci; Setyarini Santosa; Vita Elisa Fitriana (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2021)
Abstract: This research aims to find out whether the presence of independent commissioner can restrict the manipulation of earnings by management in financially distressed companies. Earning management used in this research is accrual as well as real earning management. This research employs quantitative method with data panel regression model. The sample used in this study is secondary data obtained from consumer goods industry listed on Indonesia Stock Exchange during the period of 2015 until 2019. The result of this study revealed that both accrual earnings management and real earnings management are significantly influenced by financial distress. However, independent commissioner fails to moderate the relationship of financial distress with both accrual earnings management and real earnings management. This research gives an insight and input to the management as the evaluation material, so that the earnings manipulation could be reduced or even not carried out. Abstrak: Penelitian ini bertujuan untuk mengetahui apakah keberadaan komisaris independen dapat membatasi manipulasi laba oleh manajemen pada perusahaan yang mengalami financial distress. Manajemen laba yang digunakan dalam penelitian ini adalah manajemen laba akrual dan manajemen laba riil. Penelitian ini menggunakan metode kuantitatif dengan model regresi data panel. Sampel yang digunakan dalam penelitian ini adalah data sekunder yang diperoleh dari industri barang konsumsi yang terdaftar di Bursa Efek Indonesia selama periode 2015 hingga 2019. Hasil penelitian ini mengungkapkan bahwa baik manajemen laba akrual maupun manajemen laba riil dipengaruhi secara signifikan oleh financial distress. Namun, komisaris independen gagal memoderasi hubungan financial distress dengan manajemen laba akrual dan manajemen laba riil. Penelitian ini memberikan wawasan dan masukan kepada pihak manajemen sebagai bahan evaluasi, sehingga manipulasi laba dapat dikurangi atau bahkan tidak dilakukan.